2018
DOI: 10.3390/ijms19061760
|View full text |Cite
|
Sign up to set email alerts
|

RNA-Seq Analysis Reveals a Positive Role of HTR2A in Adipogenesis in Yan Yellow Cattle

Abstract: In this study, we performed high throughput RNA sequencing at the primary bovine preadipocyte (Day-0), mid-differentiation (Day-4), and differentiated adipocyte (Day-9) stages in order to characterize the transcriptional events regulating differentiation and function. The preadipocytes were isolated from subcutaneous fetal bovine adipose tissues and were differentiated into mature adipocytes. The adipogenic characteristics of the adipocytes were detected during various stages of adipogenesis (Day-0, Day-4, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 37 publications
(40 reference statements)
0
14
0
Order By: Relevance
“…A GWAS in sheep linked a SNP close to htr1e with internal fat content ( Hernández-Montiel et al, 2020 ). In Yan Yellow cattle, RNA-seq analysis revealed a positive role for another serotonin receptor, htr2a , in adipogenesis ( Yun et al, 2018 ). In humans, genetic studies have reported that polymorphisms in Htr genes (for example, HTR1A , HTR1Dβ , and HTR2A ) are associated with obesity ( Gorwood et al, 2002 ; Levitan et al, 2006 ; Compan et al, 2012 ; Oh et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…A GWAS in sheep linked a SNP close to htr1e with internal fat content ( Hernández-Montiel et al, 2020 ). In Yan Yellow cattle, RNA-seq analysis revealed a positive role for another serotonin receptor, htr2a , in adipogenesis ( Yun et al, 2018 ). In humans, genetic studies have reported that polymorphisms in Htr genes (for example, HTR1A , HTR1Dβ , and HTR2A ) are associated with obesity ( Gorwood et al, 2002 ; Levitan et al, 2006 ; Compan et al, 2012 ; Oh et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…RNA sequence analysis showed that KLFl6 expression was decreased on the first day of adipocyte differentiation of 3T3-L1 cells. Adipocyte differentiation was promoted by KLF16 knockdown but was inhibited by KLF16 overexpression via inhibition of PPAR γ promoter activity [ 64 ]. In addition, KLF3 and KLF7 were also found to play a negative regulatory role in adipocyte differentiation [ 65 , 66 ].…”
Section: Adipocyte Differentiation Regulatory Proteinsmentioning
confidence: 99%
“…The PI3K-Akt signaling pathway is a classic insulin signaling pathway [26], and is involved in proliferation, differentiation, apoptosis, and glucose transport. Moreover, the PI3K-Akt pathway may also regulate adipogenesis [27,28]. The detailed function and regulatory mechanisms of the differentially expressed genes involved in these pathways should be carefully elucidated in subsequent studies.…”
Section: Discussionmentioning
confidence: 99%